Anthologie Plastique du Surréalisme - Baron, Jacques; Baum, Timothy (Paris : Editions Filipacchi, 1980)
Bellmer, Hans ; Brauner, Victor ; de Chirico, Giorgio ; Dali, Salvador ; Eluard, Paul ; Ernst, Max ; Man Ray ; Miró, Joan ; Picasso, Pablo ; etc.
Frans
boek